Influenza in refugees on the Thailand-Myanmar border, May-October 2009. - Turner, P; Turner, C; Watthanaworawit, W; Carrara, V; Kapella, B; Painter, J; Nosten, F (2010)
We describe the epidemiology of influenza virus infections in refugees in a camp in rural Southeast Asia during May-October 2009, the first 6 months after identification of pandemic (H1N1) 2009 in Thailand. Influenza A viruses were detected in 20% of patients who had influenza-like illness and in 23% of those who had clinical pneumonia. Seasonal influenza A (H1N1) was the predominant virus circulating during weeks 26-33 (June 25-August 29) and was subsequently replaced by the pandemic strain. A review of passive surveillance for acute respiratory infection did not show an increase in acute respiratory tract infection incidence associated with the arrival of pandemic (H1N1) 2009 in the camp.